Tribological and mechanical performance of epoxy composites reinforced with iron sand and carbon fillers: A Systematic review with experimental perspective - Willy Artha Wirawan; Dewi Puspitasari; Ayan Sabitah; Mukhlis Muslimin; Edi Widodo; R.A. Ilyas (Mechanical Engineering for Society and Industry, 2026)
Epoxy composites are widely used in structural and tribological applications because they combine good adhesion, corrosion resistance, and mechanical stability with relatively simple processing. Their main limitation is inadequate wear resistance under sustained sliding or abrasive contact. A growing body of literature therefore explores the incorporation of mineral fillers and carbon-based additives to improve both tribological and mechanical performance. This review critically examines epoxy composites reinforced with mineral iron sand and carbon fillers, with emphasis on processing routes, microstructural evolution, interfacial behavior, wear response, hardness, and flexural properties. The review also places this material system within the broader context of polymer composites used in automotive, aerospace, gears, electronics, and tribological components. Across the literature, iron-rich fillers mainly improve stiffness, hardness, and load-bearing ability, whereas carbon fillers reduce friction and facilitate the formation of lubricating transfer layers. However, the benefits are non-linear. Intermediate carbon loading often yields the best compromise between wear resistance and flexural strength, while excessive loading tends to increase agglomeration, porosity, and stress concentration. The review further re-examines common interpretations of XRD, FTIR, and SEM results and highlights important methodological limitations. Finally, it identifies research gaps related to long-term durability, fatigue, thermal cycling, surface treatment of carbon particles, and data-driven optimization of filler content for engineering applications.